Poverty, inequality, and prices in post-apartheid South Africa - Arden Finn; Murray Leibbrandt; Morné Oosthuizen (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
Post-apartheid poverty and inequality trends have been the subject of intensive analysis, yet relatively little attention has been devoted to the impact of differential price movements on the measurement of poverty and inequality. This paper aims to tell the story of the evolution of both money-metric and non-money-metric poverty and inequality in post-apartheid South Africa, and to assess the effect of prices on this story. Our results show that inflation over the latter half of the 2000s has been anti-poor and that accounting for differential price movements dampens the measured improvements in poverty and inequality.
Keywords: E31; D63; I32; 330; inequality; poverty; prices; South Africa